EXPLORING EMMA BOVARY’S DIFFUSED PERSONALITY IN GUSTAVE FLAUBERT’S MADAME BOVARY NOVEL - Tlonaen, Zuvyati Aryani (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2022)
This study aimed to explore Emma’s diffused personality in the novel Madame Bovary by Gustave Flaubert. This study used a qualitative approach. The data collection technique used documentation. The research instrument used the diffusion personality features by Kroger (2005) consisting of 12 features; low levels of autonomy, low level of self-esteem, low level of identity, having no firm identity-defining commitments nor interest in making them, demonstrate the lowest sense of personal continuity over time, difficulties in adapting to an environment, most self-focused, unsystematic approaches to solving problems, high level of neuroticism, high defense-mechanism, high level of external locus of control, and hopeless. Data analysis used content analysis. The research procedure was reading the novel, identifying the characters' behavior, thoughts, words, and action, classifying sentences or phrases that show 12 diffusion features, coding, and verification. The study showed that Emma has the twelve diffused personality features. This study proves that identity status can be detected in literary works.